Dopamine transporter SLC6A3 genotype affects cortico-striatal activity of set-shifts in Parkinson's disease. (10th September 2014) - Habak, Claudine; Noreau, Anne; Nagano-Saito, Atsuko; Mejía-Constaín, Beatriz; Degroot, Clotilde; Strafella, Antonio P.; Chouinard, Sylvain; Lafontaine, Anne-Louise; Rouleau, Guy A.; Monchi, Oury
Abstract : Parkinson's disease is a neurodegenerative condition that affects motor function along with a wide range of cognitive domains, including executive function. The hallmark of the pathology is its significant loss of nigrostriatal dopamine, which is necessary for the cortico-striatal interactions that underlie executive control. Striatal dopamine reuptake is mediated by the SLC6A3 gene (formerly named DAT1 ) and its polymorphisms, which have been largely overlooked in Parkinson's disease. Thirty patients (ages 53–68 years; 19 males, 11 females) at early stages of Parkinson's disease, were genotyped according to a 9-repeat (9R) or 10-repeat (10R) allele on the SLC6A3/DAT1 gene. They underwent neuropsychological assessment and functional magnetic resonance imaging while performing a set-shifting task (a computerized Wisconsin Card Sorting Task) that relies on fronto-striatal interactions. Patients homozygous on the 10R allele performed significantly better on working memory tasks than 9R-carrier patients. Most importantly, patients carrying a 9R allele exhibited less activation than their 10R homozygous counterparts in the prefrontal cortex, premotor cortex and caudate nucleus, when planning and executing a set-shift. This pattern was exacerbated for conditions that usually recruit the striatum compared to those that do not. This is the first study indicating that the SLC6A3/DAT1 genotype has a significant effect on fronto-striatal activation and performance in Parkinson's disease. This effect is stronger for conditions that engage the striatum. Longitudinal studies are warranted to assess this polymorphism's effect on the clinical evolution of patients with Parkinson's disease, especially with cognitive decline.